Hypereosinophilic syndrome with erythrodermia - Huayhua-Guevara, Héctor (2020)
A 77-year-old male, with a history of heart failure and atrial fibrillation receiving warfarin, hypothyroidism, diabetes mellitus and hyperuricaemia, with a one-year history of erythematous and desquamative skin lesions in the trunk, pruritic and moderate recurrent eosinophilia. After allergic, parasitic, autoimmune and neoplastic causes were ruled out, the diagnosis of idiopathic hypereosinophilic syndrome was done. He was treated with prednisone and hydroxyurea, resulting in complete remission of eosinophilia and progressive improvement of dermal lesions.